IDNLearn.com is your go-to platform for finding accurate and reliable answers. Our platform provides detailed and accurate responses from experts, helping you navigate any topic with confidence.
Sagot :
Answer:
C. (-1, 3)
Step-by-step explanation:
Label the 2 equations:
5y= 7x +22 -----(1)
x= -6y +17 -----(2)
Substitute (2) into (1):
5y= 7(-6y +17) +22
5y= -42y +119 +22 (Expand bracket)
5y= -42y +141 (Simplify)
42y +5y= 141 (+42y on both sides)
47y= 141
y= 141 ÷47 (÷47 on both sides)
y= 3
Substitute y= 3 into (2):
x= -6(3) +17
x= -18 +17
x= -1
Thus, the solution is (-1, 3).
Your engagement is important to us. Keep sharing your knowledge and experiences. Let's create a learning environment that is both enjoyable and beneficial. Your questions deserve precise answers. Thank you for visiting IDNLearn.com, and see you again soon for more helpful information.